Understanding Islam within the Malaysia concept - Ahmad Bustami, Tajul Aris; Mohamad, Nor Asiah (2011)
The government of Malaysia continues to introduce new initiative towards strengthening the multi-ethnic. The history shows that there were cases where questions on the rights and position of the respective ethnics have been raised including the position of Islam as the religion of the Federation of Malaysia. The Federal Constitution 1957 contains provision which clearly states that articles 3 of the Federal Constitution positions Islam as the official religion of the country. There are many perceptions and interpretations revolve around these two issues. Some address the permission to practice other religions as providing equal rights to all religions, including Islam. This paper promotes that 1 Malaysia concept implies that as the Federal Constitution has clearly prescribed for Islam as the religion of the Federation, as such; the position of Islam is higher than other religions. In this respect, this paper traces the various aspects where the government is entrusted to provide and argues that the government is not burdened with a duty to ensure equality of rights and treatment in all aspects concerning religion to others. Thus, the assurance that other religions may be practiced is a permission allowing the non Muslim to practice their religions without putting a responsibility on the government to ensure equal rights are given to all religions. This paper looks at the meaning and spirit of Article 3 of the Federal Constitution and the right and duties assigned to the Yang Di Pertuan Agong to protect the position of Islam as the religion of the Federation.